Older adult and family member perspectives of the decision-making process involved in moving to assisted living. (May 2014) - Koenig, Terry L; Lee, Jung Hee; Macmillan, Kelley R; Fields, Noelle L; Spano, Richard
The decision to move into assisted living (AL) can be viewed as a life-changing process for older adults and their families; and each may possess differing views of this process. This qualitative study examined the AL decision-making process as described by twenty-two older adult and family member dyads. Participants described emotional and logistical components related to the AL moving decision. Further, fifteen of twenty-two dyads expressed conflicting or differing views of the AL moving decision. Our discussion examines the need for future studies to explore the impact of family and older adult disagreements on the older adult's AL adjustment; the necessity for community-based agencies and AL settings to provide social services over the duration of the decision-making process; and the importance of employing social workers skilled in family practice in the AL setting.